Pseudomonas aeruginosa biofilms in disease - Mulcahy, Lawrence R. (2013)
Pseudomonas aeruginosa is a ubiquitous organism that is the focus of intense research because of its prominent role in disease. Due to its relatively large genome and flexible metabolic capabilities, this organism exploits numerous environmental niches. It is an opportunistic pathogen that sets upon the human host when the normal immune defenses are disabled. It’s deadliness is most apparent in cystic fibrosis patients, but it also is a major problem in burn wounds, chronic wounds, chronic obstructive pulmonary disorder (COPD), surface growth on implanted biomaterials, and within hospital surface and water supplies where it poses a host of threats to vulnerable patients [1,2]. Once established in the patient, P. aeruginosa can be especially difficult to treat. The genome encodes a host of resistance genes, including multidrug efflux pumps [3]and enzymes conferring resistance to beta-lactam and aminoglycoside antibotics [4], making therapy against this gram-negative pathogen particularly challenging due to the lack of novel antimicrobial therapeutics [5]. This challenge is compounded by the ability of P. aerugionsa to grow in a biofilm, which may enhance its ability to cause infections by protecting bacteria from host defenses and chemotherapy. Here we review recent studies of P. aeruginosa biofilms with a focus on how this unique mode of growth contributes to its ability to cause recalcitrant infections.